Agomelatine in the treatment of anhedonia, somatic symptoms, and sexual dysfunction in major depressive disorder - Huang, Juan; Xie, Xiao-Meng; Lyu, Nan; Fu, Bing-Bing; Zhao, Qian; Zhang, Ling; Wang, Gang (Frontiers in Psychiatry, 2023)
Objective: This study evaluated the treatment outcomes of agomelatine on anhedonia-state, anxiety/somatic symptoms, and sexual function in Chinese patients with major depressive disorder (MDD). Method: In total, 93 adult patients with MDD were enrolled and 68 of them were included in a prospective, open-label, multicenter clinical study. All patients received agomelatine monotherapy during 9weeks treatment phase. The efficacy of the treatment was reflected by the improvement of anhedonia and somatic symptoms were conducted by using 17-item Hamilton Depression Rating scale (HAMD-17). In addition, the Arizona Sexual Dysfunction Scale (ASEX), Sheehan Disability Scale (SDS), and the Short Form of Quality-of-Life Enjoyment and Satisfaction Questionnaire (Q-LES-Q-SF) were applied to all participants at baseline and the 3, 6 and 9-week follow-ups. Results: After 9 weeks of treatment with agomelatine, the response and remission rates were 73.5% and 39.7% respectively. The somatic symptoms were significantly improved at week 9(p < 0.001), and significant effects were also observed on the HAMD anhedonia items (p < 0.001). The patients also had lower levels of disease severity (the score of SDS dropped from 15.52 ± 4.7 to 7.09 ± 5.62 at week 9; the score of ASEX from 21.89 ± 4.06 to 16.19 ± 4.79, p < 0.001, respectively) and higher levels of QOL (the score of Q-LES-Q-SF from 41.02 ± 5.99 to 50.49 ± 8.57, p < 0.001) during follow-up. In addition, treatments of agomelatine improved depressive symptoms without causing serious adverse events. Conclusion: These analyses indicate that agomelatine is a therapeutic option for anxiety/somatic symptom, anhedonia-state, and sexual dysfunction with satisfactory efficacy and safety in patients with MDD.